Faculty roles and changing expectations in the new age - Inoue, Yukiko (IGI Global, 2019)
"This book provides theoretical understanding of the essential link between ongoing changes in institutions and changes in faculty roles, a link that is important for understanding teaching and learning in general, and for understanding learner-centered pedagogical approaches. It also provides course designs and pedagogical approaches that place faculty in the role of leaders and coaches for learning"--Provided by publisher
Description based on title screen (IGI Global, viewed 01/24/2019)
Keywords: Universities and colleges / Faculty; College teachers / In-service training; Education, Higher / Administration; Universities and colleges / Administration; Educational leadership; Educational change